Mitigation and Adaptation Practices to the Impact of Climate Change on Wine Grape Production, with Special Reference to the South African Context - Theron, H.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2022)
In South Africa, environmentally and socio-economically sustainable wine grape production is promoted by governmental and private initiatives. All the initiatives contribute to establishing a scientifically based response strategy of agro-systems to ensure sustainable production under future expected climate conditions. South African wine grape producers would probably have to cultivate their grapevines under higher atmospheric CO2 levels and in warmer, mostly drier, conditions. Due to the projected increase in climatic variability, an effort must be made to improve the resilience of vines against these environmental conditions. Whole-vine functioning and balances should be considered when adjustments are made to current long and short term cultivation practices. All practices should be aimed at promoting the development of a deep, dense and buffered root system that is able to support a well-developed canopy with optimal microclimate that would sustain a high yield of good quality. Mitigation and adaptation strategies would most likely have to be region specific, and small scale terroir data, (which should include both climate and terrain/soil information) may play a critical role in decision-making.